2009
DOI: 10.1159/000252980
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Subconjunctival Bevacizumab in Primary Pterygium Excision

Abstract: Purpose: To evaluate the efficacy of subconjunctival bevacizumab as an adjunctive therapy for primary pterygium surgery. Material and Methods: This randomized prospective clinical study was conducted on 30 eyes of 30 patients. After pterygium excision and accomplishing a rotational conjunctival flap, 15 patients (case group) received 1.25 mg (0.1 ml) bevacizumab, and 15 other patients (control group) received 0.1 ml balanced salt solution subconjunctivally. The main outcome measures were recurrence of pterygia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 65 publications
1
37
2
1
Order By: Relevance
“…Two randomized controlled trials, 12,13 1 case series, 14 and 1 case report, 15 found that subconjunctival bevacizumab reduced the symptoms and sizes of pterygia, but the effect was temporary and not clinically relevant. [12][13][14][15] Furthermore, Razeghinejad et al 16 and Shenasi et al 17 reported that subconjunctival bevacizumab used as an adjunctive therapy after primary pterygial surgery did not significantly prevent recurrence of pterygia, even though the treatment was well tolerated. The reason for this may be because of the short-term temporary effect of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled trials, 12,13 1 case series, 14 and 1 case report, 15 found that subconjunctival bevacizumab reduced the symptoms and sizes of pterygia, but the effect was temporary and not clinically relevant. [12][13][14][15] Furthermore, Razeghinejad et al 16 and Shenasi et al 17 reported that subconjunctival bevacizumab used as an adjunctive therapy after primary pterygial surgery did not significantly prevent recurrence of pterygia, even though the treatment was well tolerated. The reason for this may be because of the short-term temporary effect of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical methods for pterygium consist of the use of CAT, limbal and limbal-conjunctival transplantation, conjunctival flap and conjunctival rotation surgery, AMT, cultivated conjunctival transplantation, lamellar keratoplasty and use of fibrin glue. The medical methods include mitomycin C treatment, 5-fluorouracil and beta-irradiation, and use of anti-vascular endothelial growth factor [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival erythema was scored as 1 for moderate and 2 for severe. 6 Conjunctival flap edema, subconjunctival hemorrhage, lacrimation, and photophobia were scored as either 0, indicating absence, or 1, for presence. Any complications of conjunctival flaps such as retraction or melting and wound infection were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…12 In our previous report, subconjunctival bevacizumab (1.25 mg) caused a clinically but not statistically significant amount of corneal epithelial defect in patients who underwent pterygium excision. 6 In this study, we report the effect of a higher dose of bevacizumab with greater participants on the early postoperative wound healing after pterygium excision.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation